Trudne miejsca w nauczaniu wymowy polskiej w środowisku bułgarskojęzycznym - Mirosławska, Wirginia (Postscriptum Polonistyczne, 2020)
The article deals with phonetic mistakes made by the students of Polish at The University of Veliko Turnovo (Bulgaria). The research covers over 50 students who studied Polish in 2008–2012, with the main focus on the recurrent mistakes and their sources. Language interference is the cause of the most frequent mistakes, such as the reduction of unstressed vowels, the confusion of [ł], [l] i [ṷ], the reduction in articulation of the geminates into one short sound, incorrect palatalisation or dispalatalisation of consonants. Another source of these mistakes lies in the difficulties in recognition and articulation of sounds that do not exist in Bulgarian: nasal vowels, [y], alveolopalatals [ś], [ź], and the affricates [ć] and [1].